A glass fiber composite board for automobiles and its preparation method

By using nylon 6, polytetrafluoroethylene and other materials with modified glass fibers, reinforced fibers, etc., the extrusion molding process solves the aging and surface quality of glass fiber composite sheets, and achieves high strength, long life and excellent surface quality glass fiber composite sheets.

CN119752165APending Publication Date: 2025-04-04JIANGSU ZHONGYING NEW MATERIALS TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411788320.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing glass fiber reinforced nylon composite sheets are prone to aging during long-term use, have a short service life, and are prone to quality problems such as bubbles on the surface after forming.

Method used

The combination of nylon 6, polytetrafluoroethylene, modified glass fiber, modified reinforcement fiber, modified carbon powder, modified kaolin, rigid enhancer and compatibilizer are used to produce glass fiber composite panels through an extrusion molding process.

Benefits of technology

It improves the strength and anti-aging properties of the board, extends the service life, reduces bubble phenomena on the surface of the board, and improves the surface quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752165A_ABST
    Figure CN119752165A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of glass fiber, in particular to a glass fiber composite board for automobiles and a preparation method thereof. Aiming at the existing problems of short service life and poor surface quality, the following scheme is proposed. The composite board comprises, by weight, 20 to 30 parts of nylon 6, 15 to 25 parts of polytetrafluoroethylene, 25 to 35 parts of modified glass fiber, 15 to 20 parts of modified reinforcing fiber, 1 to 5 parts of modified carbon powder, 1 to 4 parts of modified kaolin, 1.0 to 3.0 parts of a stiffening agent and 1.0 to 2.0 parts of a compatibilizer. The material produced by the combination of nylon 6, polytetrafluoroethylene, modified glass fiber, modified reinforcing fiber, modified carbon powder, modified kaolin, stiffening agent and compatibilizer has high strength of the board after extrusion molding, good anti-aging effect, long service life, less bubbles in the produced board and excellent surface quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass fibers, and in particular to a glass fiber composite board for automobiles and a preparation method thereof. Background Art

[0002] The Chinese patent document with application number 201811406324.X discloses a continuous glass fiber reinforced nylon composite sheet, a preparation method thereof, and an application thereof in the preparation of automobile brake pedals. The raw material composition of the continuous glass fiber reinforced nylon composite sheet of the present invention includes, by weight: 100 parts of nylon 6; 100-200 parts of continuous glass fiber; 0.5-10 parts of stiffening agent; 0-2 parts of nucleating agent; 0.5-5 parts of processing aid; the stiffening agent is selected from at least one of organically modified nano calcium carbonate, organically modified nano barium sulfate, and organically modified nano montmorillonite. The continuous glass fiber reinforced nylon composite sheet prepared by the above formula combined with specific processing conditions has excellent high strength and high modulus, can be applied to the field of automobile brake pedals, and fully meets the safety requirements of automobile brake pedals.

[0003] However, the above patents also have some problems. For example, the board is prone to aging during long-term use and has a short service life, which affects the continuous use of the board. Moreover, after forming, bubbles are prone to appear on the surface of the board, and the factory needs to perform subsequent grinding and polishing. Summary of the invention

[0004] Based on the fact that the background technology has the problems of short service life and poor surface quality, the present invention proposes a glass fiber composite board for automobiles and a preparation method thereof.

[0005] The invention provides a glass fiber composite board for automobiles. The raw materials include, by weight, 20 to 30 parts of nylon 6, 15 to 25 parts of polytetrafluoroethylene, 25 to 35 parts of modified glass fiber, 15 to 20 parts of modified reinforcing fiber, 1 to 5 parts of modified carbon powder, 1 to 4 parts of modified kaolin, 1.0 to 3.0 parts of a stiffening agent and 1.0 to 2.0 parts of a compatibilizer. The modified reinforcing fiber includes poly(p-phenylene benzobisoxazole) fiber, polyimide fiber, boron carbide fiber, diphenylmethane diisocyanate and aromatic dihydroxy compound. Anhydrous ethanol is used as a solvent. Through the combination of nylon 6, polytetrafluoroethylene, modified glass fiber, modified reinforcing fiber, modified carbon powder, modified kaolin, stiffening agent and compatibilizer, the material produced after extrusion molding has high strength of the board, good anti-aging effect, long service life, less bubbles and excellent surface quality.

[0006] Preferably, the raw materials of the modified glass fiber include glass fiber and polytetrafluoroethylene resin, the weight ratio of glass fiber to polytetrafluoroethylene resin is controlled at 3:1, the glass fiber has a diameter of 5μm to 20μm, a length of 1mm to 5mm, and a refractive index of 1.57, which is convenient for modifying the glass fiber.

[0007] Preferably, the preparation method of the modified glass fiber is as follows: after the polytetrafluoroethylene resin is heated and melted, the glass fiber is immersed in the liquid polytetrafluoroethylene resin, and after drying, a layer of polytetrafluoroethylene resin is formed on the surface of the glass fiber, and finally the glass fiber is cut into short fibers. The polytetrafluoroethylene resin can enhance the performance of the glass fiber.

[0008] Preferably, the weight ratio of poly(p-phenylene benzobisoxazole) fiber, polyimide fiber, boron carbide fiber, diphenylmethane diisocyanate and aromatic dihydroxy compound in the modified reinforcing fiber is controlled at 3:2:2:2:1 to facilitate subsequent modification.

[0009] Preferably, the preparation method of the modified reinforced fiber is as follows: after obtaining poly(p-phenylene benzobisoxazole) fiber, polyimide fiber and boron carbide fiber, pour them into a reactor, then add anhydrous ethanol as a solvent, stir until the poly(p-phenylene benzobisoxazole) fiber, polyimide fiber and boron carbide fiber are evenly dispersed in the anhydrous ethanol, then add diphenylmethane diisocyanate and an aromatic dihydroxy compound, extract air and inject inert gas, then start the reactor and stir at a high speed of 600rpm to 800rpm, heat to 55°C to 65°C, mix for 15 minutes, cool naturally, remove the anhydrous ethanol to obtain the reinforced fiber, which can enhance the modification effect.

[0010] Preferably, the raw materials of the modified carbon powder include rice husks and sodium hydroxide, and anhydrous ethanol is used as a solvent. The preparation method is: after drying the rice husks, carbonizing them into qualified carbon powder using a carbonizer, then adding the carbon powder to sodium hydroxide, mixing them evenly, adding them to anhydrous ethanol, ultrasonically vibrating for 15 minutes, and drying to obtain the modified carbon powder, thereby enhancing the compatibility of the modified carbon powder.

[0011] Preferably, the raw materials of the modified kaolin include kaolin, calcium hydroxide, sodium carbonate solution, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate. The preparation method is: after kaolin is crushed, calcium hydroxide is added and mixed evenly, then poured into sodium carbonate solution and stirred evenly, allowed to stand, filtered to obtain kaolin slurry, the kaolin slurry is poured into a ball mill, and talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate are added, ball milling is performed for modification to obtain modified slurry, the modified slurry is transported to a filter press for dehydration, and then dried and crushed to obtain modified kaolin, which can enhance the performance of the plate.

[0012] A method for preparing a glass fiber composite board for an automobile comprises the following steps: S1: heating and melting nylon 6 and polytetrafluoroethylene, and mixing them to obtain an adhesive liquid; S2: then adding the modified carbon powder, modified kaolin and compatibilizer into the interior of the mixing equipment for high-speed mixing, mixing evenly, adding into the adhesive liquid and mixing again to obtain a mixture; S3: adding modified glass fiber, modified reinforcing fiber and stiffening agent into the mixture, and mixing them evenly to obtain a semi-finished product; S4: pouring the semi-finished product into the mold, extruding and molding it, and cooling and molding it to obtain a glass fiber composite panel for automobiles.

[0013] Preferably, in S2, the rotation speed of the mixing device is controlled at 800 rpm to 1000 rpm per minute, and the high-speed mixing is performed for 5 minutes to 10 minutes to ensure the mixing efficiency.

[0014] Preferably, in S3, the modified glass fiber and the modified reinforcing fiber are added and mixed for 5 minutes, and then the stiffening agent is added and mixed to enhance the performance of the board.

[0015] Beneficial effects of the present invention: Through the combination of nylon 6, polytetrafluoroethylene, modified glass fiber, modified reinforcing fiber, modified carbon powder, modified kaolin, stiffener and compatibilizer, the material produced has high strength, good anti-aging effect, long service life, fewer bubbles and excellent surface quality after extrusion molding. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The working flow chart proposed by the present invention. DETAILED DESCRIPTION

[0017] The present invention will be further explained below in conjunction with specific embodiments.

[0018] Reference Figure 1 , Embodiment 1 In this embodiment, a glass fiber composite board for automobiles is proposed. The raw materials include, by weight: 23 parts of nylon 6, 22 parts of polytetrafluoroethylene, 27 parts of modified glass fiber, 18 parts of modified reinforcing fiber, 4 parts of modified carbon powder, 2 parts of modified kaolin, 2.3 parts of stiffening agent and 1.7 parts of compatibilizer; the modified reinforcing fiber includes poly(p-phenylene benzobisoxazole) fiber, polyimide fiber, boron carbide fiber, diphenylmethane diisocyanate and aromatic dihydroxy compound, anhydrous ethanol is used as solvent, the raw materials of the modified glass fiber include glass fiber and polytetrafluoroethylene resin, the weight ratio of glass fiber to polytetrafluoroethylene resin is controlled at 3:1, and the diameter of the glass fiber is 2.30mm. The fiber is 5 μm to 20 μm, 1 mm to 5 mm in length, and has a refractive index of 1.57. The preparation method of the modified glass fiber is as follows: after the polytetrafluoroethylene resin is heated and melted, the glass fiber is immersed in the liquid polytetrafluoroethylene resin. After drying, a layer of polytetrafluoroethylene resin is formed on the surface of the glass fiber, and finally the fiber is cut into short fibers. The weight ratio of the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber, the boron carbide fiber, the diphenylmethane diisocyanate and the aromatic dihydroxy compound in the modified reinforcing fiber is controlled at 3:2:2:2:1. The preparation method of the modified reinforcing fiber is as follows: after the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber and the boron carbide fiber are obtained, they are poured into a reaction kettle, and then added Anhydrous ethanol is added as a solvent and stirred until the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber and the boron carbide fiber are uniformly dispersed in the anhydrous ethanol, then diphenylmethane diisocyanate and an aromatic dihydroxy compound are added, air is extracted and an inert gas is injected, and then the reactor is started to stir at a high speed of 600rpm to 800rpm, heated to 55°C to 65°C, mixed for 15 minutes, cooled naturally, and the anhydrous ethanol is removed to obtain the reinforced fiber. The raw materials of the modified carbon powder include rice husk and sodium hydroxide, and anhydrous ethanol is used as a solvent. The preparation method is as follows: after drying the rice husk, a carbonizer is used to carbonize it into qualified carbon powder, and then the carbon powder is added to the sodium hydroxide, and anhydrous ethanol is added after mixing evenly. The raw materials of the modified kaolin include kaolin, calcium hydroxide, sodium carbonate solution, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate. The preparation method is as follows: after kaolin is crushed, calcium hydroxide is added and mixed evenly, then poured into sodium carbonate solution and stirred evenly, allowed to stand, filtered, and kaolin slurry is obtained, the kaolin slurry is poured into a ball mill, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate are added, ball milling is performed for modification, and modified slurry is obtained, the modified slurry is transported to a filter press for dehydration, and then dried and crushed to obtain modified kaolin.

[0019] A method for preparing a glass fiber composite board for an automobile comprises the following steps: S1: heating and melting nylon 6 and polytetrafluoroethylene, and mixing them to obtain an adhesive liquid; S2: then adding the modified carbon powder, modified kaolin and compatibilizer into the interior of the mixing equipment for high-speed mixing, the speed of the mixing equipment is controlled at 900 rpm, the high-speed mixing is performed for 10 minutes, the mixture is evenly added into the adhesive liquid and mixed again to obtain a mixture; S3: adding the modified glass fiber, the modified reinforcing fiber and the stiffening agent to the mixture, mixing the modified glass fiber and the modified reinforcing fiber for 5 minutes, and then adding the stiffening agent to mix, and mixing evenly to obtain a semi-finished product; S4: pouring the semi-finished product into the mold, extruding and molding it, and cooling and molding it to obtain a glass fiber composite panel for automobiles.

[0020] Reference Figure 1 , Embodiment 2 In this embodiment, a glass fiber composite board for automobiles is proposed. The raw material composition includes, by weight: 25 parts of nylon 6, 15 parts of polytetrafluoroethylene, 32 parts of modified glass fiber, 18 parts of modified reinforcing fiber, 3 parts of modified carbon powder, 3 parts of modified kaolin, 2.4 parts of stiffening agent and 1.6 parts of compatibilizer; the modified reinforcing fiber includes poly(p-phenylene benzobisoxazole) fiber, polyimide fiber, boron carbide fiber, diphenylmethane diisocyanate and aromatic dihydroxy compound, anhydrous ethanol is used as solvent, the raw material of the modified glass fiber includes glass fiber and polytetrafluoroethylene resin, the weight ratio of glass fiber to polytetrafluoroethylene resin is controlled at 3:1, and the diameter of the glass fiber is 5μm~20μm, length is 1mm~5mm, refractive index is 1.57, preparation method of modified glass fiber: after polytetrafluoroethylene resin is heated and melted, glass fiber is immersed in liquid polytetrafluoroethylene resin, after drying, a layer of polytetrafluoroethylene resin is formed on the surface of glass fiber, and finally cut into short fibers, the weight proportion of poly(p-phenylene benzobisoxazole) fiber, polyimide fiber, boron carbide fiber, diphenylmethane diisocyanate and aromatic dihydroxy compound in modified reinforcing fiber is controlled at 3:2:2:2:1, preparation method of modified reinforcing fiber: after poly(p-phenylene benzobisoxazole) fiber, polyimide fiber and boron carbide fiber are obtained, they are poured into a reaction kettle, and then added Anhydrous ethanol is used as a solvent and stirred until poly(p-phenylene benzobisoxazole) fiber, polyimide fiber and boron carbide fiber are uniformly dispersed in the anhydrous ethanol, then diphenylmethane diisocyanate and aromatic dihydroxy compound are added, air is extracted and inert gas is injected, then the reactor is started to stir at a high speed of 600rpm to 800rpm, heated to 55°C to 65°C, mixed for 15 minutes, cooled naturally, and the anhydrous ethanol is removed to obtain the reinforced fiber, the raw materials of the modified carbon powder include rice husk and sodium hydroxide, and anhydrous ethanol is used as a solvent. The preparation method is as follows: after drying the rice husk, a carbonizer is used to carbonize it into qualified carbon powder, and then the carbon powder is added to the sodium hydroxide, mixed evenly, and then anhydrous ethanol is added The raw materials of the modified kaolin include kaolin, calcium hydroxide, sodium carbonate solution, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate. The preparation method is as follows: after kaolin is crushed, calcium hydroxide is added and mixed evenly, then poured into sodium carbonate solution and stirred evenly, allowed to stand, filtered, and kaolin slurry is obtained, the kaolin slurry is poured into a ball mill, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate are added, ball milling is performed for modification, and modified slurry is obtained, the modified slurry is transported to a filter press for dehydration, and then dried and crushed to obtain modified kaolin.

[0021] A method for preparing a glass fiber composite board for an automobile comprises the following steps: S1: heating and melting nylon 6 and polytetrafluoroethylene, and mixing them to obtain an adhesive liquid; S2: then adding the modified carbon powder, modified kaolin and compatibilizer into the interior of the mixing equipment for high-speed mixing, the speed of the mixing equipment is controlled at 900 rpm, the high-speed mixing is performed for 10 minutes, the mixture is evenly added into the adhesive liquid and mixed again to obtain a mixture; S3: adding the modified glass fiber, the modified reinforcing fiber and the stiffening agent to the mixture, mixing the modified glass fiber and the modified reinforcing fiber for 5 minutes, and then adding the stiffening agent to mix, and mixing evenly to obtain a semi-finished product; S4: pouring the semi-finished product into the mold, extruding and molding it, and cooling and molding it to obtain a glass fiber composite panel for automobiles.

[0022] Reference Figure 1 , Embodiment 3 In this embodiment, a glass fiber composite board for automobiles is proposed. The raw materials include, by weight: 25 parts of nylon 6, 20 parts of polytetrafluoroethylene, 25 parts of modified glass fiber, 20 parts of modified reinforcing fiber, 2 parts of modified carbon powder, 4 parts of modified kaolin, 2.5 parts of stiffener and 1.5 parts of compatibilizer; the modified reinforcing fiber includes poly(p-phenylene benzobisoxazole) fiber, polyimide fiber, boron carbide fiber, diphenylmethane diisocyanate and aromatic dihydroxy compound, anhydrous ethanol is used as solvent, the raw materials of the modified glass fiber include glass fiber and polytetrafluoroethylene resin, the weight ratio of glass fiber to polytetrafluoroethylene resin is controlled at 3:1, and the diameter of the glass fiber is 2.5:1. The fiber is 5 μm to 20 μm, 1 mm to 5 mm in length, and has a refractive index of 1.57. The preparation method of the modified glass fiber is as follows: after the polytetrafluoroethylene resin is heated and melted, the glass fiber is immersed in the liquid polytetrafluoroethylene resin. After drying, a layer of polytetrafluoroethylene resin is formed on the surface of the glass fiber, and finally the fiber is cut into short fibers. The weight ratio of the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber, the boron carbide fiber, the diphenylmethane diisocyanate and the aromatic dihydroxy compound in the modified reinforcing fiber is controlled at 3:2:2:2:1. The preparation method of the modified reinforcing fiber is as follows: after the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber and the boron carbide fiber are obtained, they are poured into a reaction kettle, and then added Anhydrous ethanol is added as a solvent and stirred until the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber and the boron carbide fiber are uniformly dispersed in the anhydrous ethanol, then diphenylmethane diisocyanate and an aromatic dihydroxy compound are added, air is extracted and an inert gas is injected, and then the reactor is started to stir at a high speed of 600rpm to 800rpm, heated to 55°C to 65°C, mixed for 15 minutes, cooled naturally, and the anhydrous ethanol is removed to obtain the reinforced fiber. The raw materials of the modified carbon powder include rice husk and sodium hydroxide, and anhydrous ethanol is used as a solvent. The preparation method is as follows: after drying the rice husk, a carbonizer is used to carbonize it into qualified carbon powder, and then the carbon powder is added to the sodium hydroxide, and anhydrous ethanol is added after mixing evenly. The raw materials of the modified kaolin include kaolin, calcium hydroxide, sodium carbonate solution, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate. The preparation method is as follows: after kaolin is crushed, calcium hydroxide is added and mixed evenly, then poured into sodium carbonate solution and stirred evenly, allowed to stand, filtered, and kaolin slurry is obtained, the kaolin slurry is poured into a ball mill, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate are added, ball milling is performed for modification, and modified slurry is obtained, the modified slurry is transported to a filter press for dehydration, and then dried and crushed to obtain modified kaolin.

[0023] A method for preparing a glass fiber composite board for an automobile comprises the following steps: S1: heating and melting nylon 6 and polytetrafluoroethylene, and mixing them to obtain an adhesive liquid; S2: then adding the modified carbon powder, modified kaolin and compatibilizer into the interior of the mixing equipment for high-speed mixing, the speed of the mixing equipment is controlled at 900 rpm, the high-speed mixing is performed for 10 minutes, the mixture is evenly added into the adhesive liquid and mixed again to obtain a mixture; S3: adding the modified glass fiber, the modified reinforcing fiber and the stiffening agent to the mixture, mixing the modified glass fiber and the modified reinforcing fiber for 5 minutes, and then adding the stiffening agent to mix, and mixing evenly to obtain a semi-finished product; S4: pouring the semi-finished product into the mold, extruding and molding it, and cooling and molding it to obtain a glass fiber composite panel for automobiles.

[0024] Reference Figure 1 , Embodiment 4 In this embodiment, a glass fiber composite board for automobiles is proposed. The raw material composition includes, by weight: 20 parts of nylon 6, 20 parts of polytetrafluoroethylene, 31 parts of modified glass fiber, 19 parts of modified reinforcing fiber, 3 parts of modified carbon powder, 4 parts of modified kaolin, 1.7 parts of stiffening agent and 1.3 parts of compatibilizer; the modified reinforcing fiber includes poly(p-phenylene benzobisoxazole) fiber, polyimide fiber, boron carbide fiber, diphenylmethane diisocyanate and aromatic dihydroxy compound, anhydrous ethanol is used as solvent, the raw material of the modified glass fiber includes glass fiber and polytetrafluoroethylene resin, the weight ratio of glass fiber to polytetrafluoroethylene resin is controlled at 3:1, and the diameter of the glass fiber is 200 μm. The fiber is 5 μm to 20 μm, 1 mm to 5 mm in length, and has a refractive index of 1.57. The preparation method of the modified glass fiber is as follows: after the polytetrafluoroethylene resin is heated and melted, the glass fiber is immersed in the liquid polytetrafluoroethylene resin. After drying, a layer of polytetrafluoroethylene resin is formed on the surface of the glass fiber, and finally the fiber is cut into short fibers. The weight ratio of the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber, the boron carbide fiber, the diphenylmethane diisocyanate and the aromatic dihydroxy compound in the modified reinforcing fiber is controlled at 3:2:2:2:1. The preparation method of the modified reinforcing fiber is as follows: after the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber and the boron carbide fiber are obtained, they are poured into a reaction kettle, and then added Anhydrous ethanol is added as a solvent and stirred until the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber and the boron carbide fiber are uniformly dispersed in the anhydrous ethanol, then diphenylmethane diisocyanate and an aromatic dihydroxy compound are added, air is extracted and an inert gas is injected, and then the reactor is started to stir at a high speed of 600rpm to 800rpm, heated to 55°C to 65°C, mixed for 15 minutes, cooled naturally, and the anhydrous ethanol is removed to obtain the reinforced fiber. The raw materials of the modified carbon powder include rice husk and sodium hydroxide, and anhydrous ethanol is used as a solvent. The preparation method is as follows: after drying the rice husk, a carbonizer is used to carbonize it into qualified carbon powder, and then the carbon powder is added to the sodium hydroxide, and anhydrous ethanol is added after mixing evenly. The raw materials of the modified kaolin include kaolin, calcium hydroxide, sodium carbonate solution, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate. The preparation method is as follows: after kaolin is crushed, calcium hydroxide is added and mixed evenly, then poured into sodium carbonate solution and stirred evenly, allowed to stand, filtered, and kaolin slurry is obtained, the kaolin slurry is poured into a ball mill, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate are added, ball milling is performed for modification, and modified slurry is obtained, the modified slurry is transported to a filter press for dehydration, and then dried and crushed to obtain modified kaolin.

[0025] A method for preparing a glass fiber composite board for an automobile comprises the following steps: S1: heating and melting nylon 6 and polytetrafluoroethylene, and mixing them to obtain an adhesive liquid; S2: then adding the modified carbon powder, modified kaolin and compatibilizer into the interior of the mixing equipment for high-speed mixing, the speed of the mixing equipment is controlled at 900 rpm, the high-speed mixing is performed for 10 minutes, the mixture is evenly added into the adhesive liquid and mixed again to obtain a mixture; S3: adding the modified glass fiber, the modified reinforcing fiber and the stiffening agent to the mixture, mixing the modified glass fiber and the modified reinforcing fiber for 5 minutes, and then adding the stiffening agent to mix, and mixing evenly to obtain a semi-finished product; S4: pouring the semi-finished product into the mold, extruding and molding it, and cooling and molding it to obtain a glass fiber composite panel for automobiles.

[0026] Reference Figure 1 Embodiment 5 In this embodiment, a glass fiber composite board for automobiles is proposed. The raw material composition includes, by weight: 25 parts of nylon 6, 25 parts of polytetrafluoroethylene, 24 parts of modified glass fiber, 16 parts of modified reinforcing fiber, 5 parts of modified carbon powder, 2 parts of modified kaolin, 2.0 parts of stiffening agent and 1.0 part of compatibilizer; the modified reinforcing fiber includes poly(p-phenylene benzobisoxazole) fiber, polyimide fiber, boron carbide fiber, diphenylmethane diisocyanate and aromatic dihydroxy compound, anhydrous ethanol is used as solvent, the raw material of the modified glass fiber includes glass fiber and polytetrafluoroethylene resin, the weight ratio of glass fiber to polytetrafluoroethylene resin is controlled at 3:1, and the diameter of the glass fiber is 2.5-3.5mm. The fiber is 5 μm to 20 μm, 1 mm to 5 mm in length, and has a refractive index of 1.57. The preparation method of the modified glass fiber is as follows: after the polytetrafluoroethylene resin is heated and melted, the glass fiber is immersed in the liquid polytetrafluoroethylene resin. After drying, a layer of polytetrafluoroethylene resin is formed on the surface of the glass fiber, and finally the fiber is cut into short fibers. The weight ratio of the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber, the boron carbide fiber, the diphenylmethane diisocyanate and the aromatic dihydroxy compound in the modified reinforcing fiber is controlled at 3:2:2:2:1. The preparation method of the modified reinforcing fiber is as follows: after the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber and the boron carbide fiber are obtained, they are poured into a reaction kettle, and then added Anhydrous ethanol is added as a solvent and stirred until the poly(p-phenylene benzobisoxazole) fiber, the polyimide fiber and the boron carbide fiber are uniformly dispersed in the anhydrous ethanol, then diphenylmethane diisocyanate and an aromatic dihydroxy compound are added, air is extracted and an inert gas is injected, and then the reactor is started to stir at a high speed of 600rpm to 800rpm, heated to 55°C to 65°C, mixed for 15 minutes, cooled naturally, and the anhydrous ethanol is removed to obtain the reinforced fiber. The raw materials of the modified carbon powder include rice husk and sodium hydroxide, and anhydrous ethanol is used as a solvent. The preparation method is as follows: after drying the rice husk, a carbonizer is used to carbonize it into qualified carbon powder, and then the carbon powder is added to the sodium hydroxide, and anhydrous ethanol is added after mixing evenly. The raw materials of the modified kaolin include kaolin, calcium hydroxide, sodium carbonate solution, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate. The preparation method is as follows: after kaolin is crushed, calcium hydroxide is added and mixed evenly, then poured into sodium carbonate solution and stirred evenly, allowed to stand, filtered, and kaolin slurry is obtained, the kaolin slurry is poured into a ball mill, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate are added, ball milling is performed for modification, and modified slurry is obtained, the modified slurry is transported to a filter press for dehydration, and then dried and crushed to obtain modified kaolin.

[0027] A method for preparing a glass fiber composite board for an automobile comprises the following steps: S1: heating and melting nylon 6 and polytetrafluoroethylene, and mixing them to obtain an adhesive liquid; S2: then adding the modified carbon powder, modified kaolin and compatibilizer into the interior of the mixing equipment for high-speed mixing, the speed of the mixing equipment is controlled at 900 rpm, the high-speed mixing is performed for 10 minutes, the mixture is evenly added into the adhesive liquid and mixed again to obtain a mixture; S3: adding the modified glass fiber, the modified reinforcing fiber and the stiffening agent to the mixture, mixing the modified glass fiber and the modified reinforcing fiber for 5 minutes, and then adding the stiffening agent to mix, and mixing evenly to obtain a semi-finished product; S4: pouring the semi-finished product into the mold, extruding and molding it, and cooling and molding it to obtain a glass fiber composite panel for automobiles.

[0028] Comparing conventional XXX with XXX obtained in Examples 1 to 5, XXX obtained in Examples 1 to 5 are shown in the following table: Comparative Example Embodiment 1 Embodiment 2 Embodiment 3 Embodiment 4 Embodiment 5 Service life of industrial load-bearing panels (years) ≥2 ≥3 ≥3 ≥3 ≥3 ≥3 Surface quality (visual observation) More bubbles Few bubbles Few bubbles Few bubbles Few bubbles Few bubbles It can be seen from the above table that the service life and surface quality of the glass fiber composite board prepared by the present invention are significantly improved.

[0029] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A glass fiber composite panel for automobiles, characterized in that: The raw material composition includes, by weight: 20 to 30 parts of nylon 6, 15 to 25 parts of polytetrafluoroethylene, 25 to 35 parts of modified glass fiber, 15 to 20 parts of modified reinforcing fiber, 1 to 5 parts of modified carbon powder, 1 to 4 parts of modified kaolin, 1.0 to 3.0 parts of stiffener and 1.0 to 2.0 parts of compatibilizer; the modified reinforcing fiber includes poly(p-phenylene benzobisoxazole) fiber, polyimide fiber, boron carbide fiber, diphenylmethane diisocyanate and aromatic dihydroxy compound, and anhydrous ethanol is used as solvent.

2. The glass fiber composite panel for automobiles according to claim 1, characterized in that: The raw materials of the modified glass fiber include glass fiber and polytetrafluoroethylene resin, the weight ratio of glass fiber to polytetrafluoroethylene resin is controlled at 3:1, the glass fiber has a diameter of 5 μm to 20 μm, a length of 1 mm to 5 mm, and a refractive index of 1.

57.

3. The glass fiber composite panel for automobiles according to claim 2, characterized in that: The preparation method of the modified glass fiber is as follows: after the polytetrafluoroethylene resin is heated and melted, the glass fiber is immersed in the liquid polytetrafluoroethylene resin, and after drying, a layer of polytetrafluoroethylene resin is formed on the surface of the glass fiber, and finally the glass fiber is cut into short fibers.

4. The glass fiber composite panel for automobiles according to claim 1, characterized in that: The weight ratio of poly(p-phenylene benzobisoxazole) fiber, polyimide fiber, boron carbide fiber, diphenylmethane diisocyanate and aromatic dihydroxy compound in the modified reinforcing fiber is controlled at 3:2:2:2:

1.

5. The glass fiber composite panel for automobiles according to claim 4, characterized in that: The preparation method of the modified reinforced fiber comprises the following steps: after obtaining poly(p-phenylene benzobisoxazole) fiber, polyimide fiber and boron carbide fiber, pouring them into a reaction kettle, then adding anhydrous ethanol as a solvent, stirring until the poly(p-phenylene benzobisoxazole) fiber, polyimide fiber and boron carbide fiber are uniformly dispersed in the anhydrous ethanol, then adding diphenylmethane diisocyanate and an aromatic dihydroxy compound, extracting air and injecting inert gas, then starting the reaction kettle to stir at a high speed of 600 rpm to 800 rpm, heating to 55° C. to 65° C., mixing for 15 minutes, cooling naturally, and removing the anhydrous ethanol to obtain the reinforced fiber.

6. The glass fiber composite panel for automobiles according to claim 1, characterized in that: The raw materials of the modified carbon powder include rice husk and sodium hydroxide, and anhydrous ethanol is used as a solvent. The preparation method is as follows: after drying the rice husk, a carbonizing machine is used to carbonize it into qualified carbon powder, and then the carbon powder is added to the sodium hydroxide, mixed evenly, and then added to the anhydrous ethanol, ultrasonically oscillated for 15 minutes, and dried to obtain the modified carbon powder.

7. The glass fiber composite panel for automobiles according to claim 1, characterized in that: The raw materials of the modified kaolin include kaolin, calcium hydroxide, sodium carbonate solution, talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate. The preparation method is: after kaolin is crushed, calcium hydroxide is added and mixed evenly, then poured into sodium carbonate solution and stirred evenly, allowed to stand, filtered to obtain kaolin slurry, the kaolin slurry is poured into a ball mill, and talcum powder, quaternary ammonium salt, titanium aluminum metal oxide, polyethylene glycol esterified lanolin and imidazoline type sodium phosphate are added, ball milling is performed for modification to obtain modified slurry, the modified slurry is transported to a filter press for dehydration, and then dried and crushed to obtain modified kaolin.

8. A method for preparing a glass fiber composite board for automobiles as claimed in claim 1, characterized in that: The following steps are involved: S1: heating and melting nylon 6 and polytetrafluoroethylene, and mixing them to obtain an adhesive liquid; S2: then adding the modified carbon powder, modified kaolin and compatibilizer into the interior of the mixing equipment for high-speed mixing, mixing evenly, adding into the adhesive liquid and mixing again to obtain a mixture; S3: adding modified glass fiber, modified reinforcing fiber and stiffening agent into the mixture, and mixing them evenly to obtain a semi-finished product; S4: pouring the semi-finished product into the mold, extruding and molding it, and cooling and molding it to obtain a glass fiber composite panel for automobiles.

9. The method for preparing a glass fiber composite board for automobiles according to claim 8, characterized in that: In S2, the rotation speed of the mixing device is controlled at 800 rpm to 1000 rpm per minute, and the high-speed mixing is performed for 5 minutes to 10 minutes.

10. The method for preparing a glass fiber composite board for automobiles according to claim 8, characterized in that: In S3, the modified glass fiber and the modified reinforcing fiber are added and mixed for 5 minutes, and then the stiffening agent is added and mixed.

Citation Information

Patent Citations

  • A continuous glass fiber reinforced nylon composite sheet, its preparation method, and its application in the manufacture of automotive brake pedals.

    CN109651804B